Improving results from digital channels - Tod, Matthew (Henry Stewart Talks, 2010)
Improving results from digital channels, Monetary value of optimization, Techniques for insight, Choosing a web analytics tool, Deploying a web analytics tool, Using web analytics data, Insight techniques, Voice of customer, Testing improvements, Optimization process
Archived at 2022/04/12